Sex-dependent and chronic alterations in behavior and mitochondrial function in a rat model of pediatric mild traumatic brain injury. (21st March 2019) - Fraunberger, Erik A.; Shutt, Timothy E.; Esser, Michael J.
ABSTRACT: Objective: To determine if chronic changes in mitochondrial function occur following a mild traumatic brain injury in young rats. Research Design: Closed-head, weight drop model was used to cause mTBI by applying rotational forces to the brain without surgery. Behavioral battery was used to assess multiple dimensions of impairment across time. Analysis of brain tissue carried out at three-weeks post-injury represents a chronic time point to complement previous work examining acute time points. Methods and Procedures: Twenty-three male and 22 female rats one month of age were divided equally into sham and mTBI groups with the latter undergoing the weight drop. Multiple behavioral tests in combination with energetic (oxygen consumption), molecular (immunoblotting), and imaging (electron microscopy) characterization of brain mitochondria were performed. Main Outcomes and Results: Mitochondria isolated from sham juvenile female rats had higher basal oxygen consumption compared to juvenile male rats (514.875 ± 171.091 pmol/min vs. 267 ± 73.906 pmol/min, p < 0.0001). Chronic sex-dependent differences were observed in females after mTBI in basal (514.875 ± 171.091 pmol/min vs. 600.688 ± 124.422 pmol/min, p = 0.0264) and maximal oxygen consumption (298.938 ± 119.964 pmol/min vs. 403.281 ± 112.922 pmol/min, p = 0.0001) and proton leak (59.46 ± 7.807 vs. 84.32 ± 5.80 pmol/min, p = 0.0001). Conclusions: The juvenile rat brain displays sex differences in mitochondrial function at (1) baseline and (2) in long-term outcomes after mTBI. These results offer new insight into a potential mechanism for persistent, individualized impairments following pediatric mTBI.